Public investment in developing countries: A blessing or a curse? - Eduardo Cavallo; Christian Daude (Inter-American Development Bank, Research Department, 2008)
This paper analyzes the impact of public investment on private investment in panel of 116 developing countries between 1980 and 2006 using dynamic panel data techniques, finding a strong and robust crowding-out effect that seems to be the norm rather than the exception, both across regions and over time. It is also found that this effect is dampened (or even reversed) in countries with better institutions and that are more open to international trade and financial flows. These results are consistent with the hypothesis that, while public infrastructure may be complementary to private capital in the aggregate production function, there are distortions associated with the public investment process that might render a crowding out of private investment in the course of building public capital stocks. These distortions, in turn, are more prevalent in countries with worse institutions or that lack trade and financial openness.
Keywords: E22; H54; H41; O16; 330; public investment; crowding out; institutions; openness; Öffentliche Investition; Crowding out; Institutionalismus; Offene Volkswirtschaft; Entwicklungsländer